Exploration of Ethnomathematics in Kobhung Madura - Ulfi Syamsiyatul Maghfiroh; Moh. Zayyadi; Sri Indriati Hasanah (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
The integration of education and culture is one of the rapidly developing fields of mathematics research today, especially through studies of traditional architecture such as Madurese kobhung. This study aims to describe the forms and patterns of ethnomathematics contained in the kobhung structures of the Madurese community. This approach is important because it can help students understand abstract geometric concepts through their connection with Madurese local wisdom. This study aims to describe the mathematical concepts found in the structure and patterns of the Madurese kobhung and map out how these concepts can be used in the mathematics learning process. The method used is qualitative research with an ethnographic approach. The research subjects are 10 Madurese informants in Pamekasan and authentic kobhung structures as purposive samples. Data collection methods included direct participatory observation in the field, in-depth interviews, visual documentation, and literature study. The main instrument was the researcher as a human instrument. Data analysis followed the Miles and Huberman model, which included data reduction, data presentation, and conclusion drawing with source triangulation validation and reliability through retesting. The results of this study describe Madurese kobhung as containing mathematical elements, namely straight/parallel lines, acute/obtuse/right angles, flat shapes (rectangles, isosceles triangles, trapezoids), congruence, geometric transformations, and the Pythagorean theorem in the pracik structure. The ethnomathematical study of kobhung in geometry learning shows that this traditional architecture can be used as a context for mathematics learning, so that the material taught becomes more contextual and has cultural meaning. This study is still limited to identifying ethnomathematical elements in the Madurese kobhung structure and has not examined its application and effectiveness in classroom learning. Therefore, the researchers recommend further research on its implementation in mathematics classroom learning.